‘If fake food doesn’t kill you, just eat it.’: Consumer perceptions and normalisation of food fraud in Nigeria - Blessing A. Okonji; Shingai Nyarugwe; Carol A. Wallace; Kemka H. Ogbonda; Jan Mei Soon-Sinclair (Food and Humanity, 2026)

Late Cenozoic erosion rates in the Western Alps revealed by detrital apatite fission-track analysis - H.D. Sinclair; M. Naylor; L.A. Kirstein; A. Carter; S. Stanton; C. Glotzbach; M. Bernet; P.A. van der Beek (Earth and Planetary Science Letters, 2026)

Detection of propadiene (CH2CCH2), propene (C3H6) and non-detection of propane (C3H8) in Jupiter’s northern polar stratosphere - James A. Sinclair; Thomas K. Greathouse; Rohini S. Giles; Keeyoon Sung; Conor A. Nixon; Nicholas A. Lombardo; Vincent Hue; Julianne I. Moses; Leigh N. Fletcher; Patrick G.J. Irwin; Glenn S. Orton (Icarus, 2026)

A white shark’s view: insights into the behaviour of a marine predator - Adrienne Gooden; Charlie Huveneers; Lucan Sinclair; Paul A. Butcher (Frontiers in Marine Science, 2026)
Animal-borne cameras are effective tools to study the fine-scale behavior and habitat use of a wide range of marine taxa, including birds, mammals, sea turtles, and elasmobranchs. We deployed animal-borne camera and accelerometer packages on 13 juvenile white sharks ( Carcharodon carcharias ; 174–283 cm total length) along the coast of New South Wales (Australia) to investigate white shark foraging behavior and habitat preferences. We annotated and assigned every second of footage to specific behaviors (e.g., swimming direction, foraging behavior) and environmental variables (e.g., habitat type) and recorded interactions with other species. From the 68.5 h of footage obtained, we identified 20 burst events (0.1% of the total time), but a potential prey was visible in only three of these instances (15% of burst events). Moreover, 10 of these burst events (50%) were along the seafloor without substantial changes in shark depth, potentially linked to benthic foraging behavior. White sharks mostly occupied sandy, low-complex habitats, which could be driven by prey availability, e.g., benthic elasmobranchs, or the ease of navigation compared to more complex environments. Our findings provide new insights into the foraging ecology and habitat use of juvenile white sharks and document novel interspecific interactions, highlighting the utility of animal-borne cameras in capturing behaviors that are otherwise difficult to observe.

How much Copper Do Calves Need? Retention and Hepatic Storage in Artificially Reared Milk-Fed Holstein–Friesian Calves - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; Stefan E. Yerby; James A. Huntington; James H. McCaughern (Biological Trace Element Research, 2026)
Excessive copper (Cu) absorption in calves may increase the risk of excessive hepatic Cu accumulation, likely driven by their elevated pre-ruminant absorptive capacity, with the potential for harmful Cu accumulation leading to adverse health and productivity outcomes. However, quantitative data across the weaning transition remains limited. This study utilized secondary data and bio-banked samples from 35 Holstein–Friesian bull calves to estimate hepatic Cu retention coefficients pre- and post-weaning. Although mean hepatic Cu concentrations remained broadly stable throughout the study, between 311 and 675 mg/kg of DM, changes varied by developmental stage: calves experienced hepatic Cu accumulation of 2.5 mg of Cu/kg of DM/d pre-weaning but a net reduction of 1.8 mg/kg of DM/d post-weaning. Pre-weaning calves exhibited a hepatic Cu retention coefficient of 81% compared to post-weaning calves, where the hepatic Cu retention coefficient was 5%. This reduction in absorptive capacity is consistent with increased rumen development and greater antagonism from dietary sulfur and molybdenum. Hepatic steady-state Cu intake requirements were estimated at 3 mg/kg of DM pre-weaning and 15 mg/kg of DM post-weaning. These findings demonstrate that the pre-weaning period represents a phase of high Cu retention and heightened susceptibility to hepatic Cu accumulation, even when dietary Cu meets current recommendations. Refining Cu feeding guidelines to more accurately reflect developmental stage and rumen maturation may help prevent excessive hepatic Cu loading while maintaining adequate mineral supply.

Effects of two methods of tooth resection on tooth integrity and piglet behaviour immediately before and after treatment - Anna R.L. Sinclair; Céline Tallet; Paula J. Brunton; Richard B. D’Eath; Dale A. Sandercock; Armelle Prunier (Applied Animal Behaviour Science, 2026)

Manipulating attention during eating effects food intake and medial prefrontal cortex fNIRS response in women with cognitive restraint - Eram Albajri; Hasan Ayaz; Patricia A. Shewokis; Angelo Del Parigi; Sinclair A. Smith; Jennifer J. Quinlan; Jennifer A. Nasser (Appetite, 2026)

M3FNet: Multi-modal multi-temporal multi-scale data fusion network for tree species composition mapping - Yuwei Cao; Nicholas C. Coops; Brent A. Murray; Ian Sinclair; Robere-McGugan Geordie (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Recovering European River Invertebrate Communities Homogenize or Differentiate Depending on Anthropogenic Stress - Daniela Cortés‐Guzmán; Diana E. Bowler; Marie Anne Eurie Forio; Peter Goethals; Ioannis Karaouzas; Ariane Moulinec; James S. Sinclair; Rudy Vannevel; Peter Haase; Ellen A. R. Welti (Global Change Biology, 2026)
Biodiversity loss can lead to biotic homogenization, whereby local communities within a region become increasingly similar over time, resulting in simplified communities with reduced functionality. However, our understanding of whether alleviating anthropogenic stress can reverse homogenization and promote biotic differentiation (i.e., increasing dissimilarity) remains limited, partly because the effectiveness of conservation actions is often assessed only at the local scale (e.g., increases in local diversity). Here, we examined evidence for biotic differentiation in European river invertebrate communities, a system that has generally shown signs of local recovery. We analyzed 447 time series of river invertebrate communities from 1994 to 2023, spanning 48 river basins across 15 European countries. We then related trends in community similarity within each basin, measured as taxonomic and trait β‐diversity, to spatial gradients of anthropogenic stress, including ecological quality (a proxy of general anthropogenic stress), air temperature increase, and land cover pressure. β‐diversity trends were strongly mediated by anthropogenic stress levels, with communities in lower‐stress basins showing differentiation, while those in higher‐stress basins homogenized. In addition, we found that the direction of β‐diversity change depended less on taxa or traits being gained or lost, and more on the identity of the traits involved, highlighting how trait composition mediates community responses to anthropogenic change. Specifically, additions promoted differentiation at lower stress levels but contributed to homogenization under conditions of higher stress, whereas subtractions exhibited the inverse pattern. Our results demonstrate that β‐diversity responds asymmetrically to spatial variation in anthropogenic stress, with both homogenization and differentiation occurring within a system that is, overall, undergoing recovery. Recognizing the stress‐dependent responses of β‐diversity allows researchers and managers to more accurately assess conservation success and provide recommendations that promote long‐term ecosystem structural and functional recovery.

Enhancing tree species composition mapping using Sentinel-2 and multi-seasonal deep learning fusion - Yuwei Cao; Nicholas C. Coops; Brent A. Murray; Ian Sinclair (International Journal of Remote Sensing, 2025)

A Lagrangian view on severe haze in Beijing: local and long-range sources of trace gases and primary and secondary aerosols - Benjamin Foreback; Petri Clusius; Metin Baykara; Alexander Mahura; Lukas Pichelstorfer; Carlton Xavier; Putian Zhou; Tom V. Kokkonen; Veli-Matti Kerminen; Yongchun Liu; Men Xia; Xin Chen; et al. (Atmospheric Environment, 2025)

The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

The discovery of a genetically distinct subpopulation of Haast tokoeka (Southern brown kiwi, Apteryx australis ‘Haast’) - Talia Brav-Cubitt; Heath M. Sinclair; Hugh A. Robertson; Andrew J. Veale (Conservation Genetics, 2025)
The Haast tokoeka ( Apteryx australis ‘Haast’) is a threatened evolutionarily significant unit (ESU) of tokoeka or southern brown kiwi in Aotearoa New Zealand. In this study, we investigated the genetic relationships of a small newly discovered population of tokoeka located at Junction Hill near Haast, which is geographically isolated from other tokoeka populations. Using pin feathers collected from five individuals at Junction Hill, we analysed 15 microsatellite loci and 1283 base pairs from two mitochondrial DNA loci (control region and cytochrome b ( Cytb )) to compare our results with those previously generated for Haast ( n = 49), northern Fiordland ( n = 7), southern Fiordland ( n = 4), and Rakiura ( n = 12) tokoeka. Our results show that the Junction Hill individuals are Haast tokoeka, but display genetic differentiation in Principle Component Analysis (PCA) and genetic assignment plots from the nearest Haast tokoeka population 18 km away in the Upper Arawhata Valley. The five Junction Hill individuals all possess a unique mitochondrial DNA haplotype that has not been observed previously. The mean allelic richness of the Junction Hill population (1.82) was slightly lower compared to the main Haast population (2.13). The presence of the Junction Hill population provides both numerical and range increases for the Haast tokoeka, and potentially contributes valuable new genetic diversity to the taxon. Further monitoring and conservation actions, such as increased pest control and translocations, may be necessary to ensure the preservation of this population and its unique genetic traits.

Fission‐Fusion Group Dynamics and Cooperative Hunting Stabilise Social Carnivore Populations - J. M. Fryxell; S. Mduma; J. Masoy; J. Grant C. Hopcraft; A. R. E. Sinclair; R. Dejeante; C. Packer (Ecology Letters, 2025)
Theory suggests that large social groups of carnivores should be unsustainable, due to reduced foraging efficiency because of overlapping perception radii. Using Serengeti lions as a case study, we apply behaviourally based foraging models to show that fragmentation of social groups into smaller subgroups or mutual cooperation during hunting are both plausible hypothetical mechanisms capable of sustaining larger lion prides. Data from the Serengeti ecosystem demonstrate that lion prides typically fragment into small hunting groups that are well approximated by an exponential distribution of group sizes typical of fission‐fusion social systems. A model linking fission‐fusion group dynamics with predator–prey interaction predicts both the surprising degree of population stability of the Serengeti lions as well as the long‐term persistence of large prides. There is little evidence, however, that Serengeti lions cooperate during hunting except when they hunt Cape buffalo, so fission‐fusion is apparently the dominant stabilising process in Serengeti.

Effects of land cover and protected areas on flying insect diversity - James S. Sinclair; Dominik Buchner; Mark O. Gessner; Jörg Müller; Steffen U. Pauls; Stefan Stoll; Ellen A. R. Welti; Claus Bässler; Jörn Buse; Frank Dziock; Julian Enss; Thomas Hörren; et al. (Conservation Biology, 2025)
Widespread insect losses are a critical global problem. Mitigating this problem requires identifying the principal drivers across different taxa and determining which insects are covered by protected areas. However, doing so is hindered by missing information on most species owing to extremely high insect diversity and difficulties in morphological identification. To address this knowledge gap, we used one of the most comprehensive insect DNA metabarcoding data sets assembled (encompassing 31,846 flying insect species) in which data were collected from a network of 75 Malaise traps distributed across Germany. Collection sites encompass gradients of land cover, weather, and climate, along with differences in site protection status, which allowed us to gain broader insights into how insects respond to these factors. We examined changes in total insect biomass, species richness, temporal turnover, and shifts in the composition of taxa, key functional groups (pollinators, threatened species, and invasive species), and feeding traits. Lower insect biomass generally equated to lower richness of all insects and higher temporal turnover, suggesting that biomass loss translates to biodiversity loss and less stable communities. Spatial variability in insect biomass and composition was primarily driven by land cover, rather than weather or climate change. As vegetation and land‐cover heterogeneity increased, insect biomass increased by 50% in 2019 and 56% in 2020 and total species richness by 58% and 33%, respectively. Similarly, areas with low‐vegetation habitats exhibited the highest richness of key taxa, including pollinators and threatened species, and the widest variety of feeding traits. However, these habitats tended to be less protected despite their higher diversity. Our results highlight the value of heterogeneous low vegetation for promoting overall insect biomass and diversity and that better protection of insects requires improved protection and management of unforested areas, where many biodiversity hotspots and key taxa occur.

A Re-evaluation of the Optimal Liver Copper Concentrations for Health, Performance and Fertility of Replacement Holstein–Friesian Heifers - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; James H. McCaughern (Biological Trace Element Research, 2025)

Understanding the role qualitative methods can play in next generation impact assessment - Heidi Walker; Alan Bond; A. John Sinclair; Alan P. Diduck; Jenny Pope; Francois Retief; Angus Morrison-Saunders (Environmental Impact Assessment Review, 2025)

Does jurisdictional siloing increase or undermine the efficiency and efficacy of next-generation IA in federalist states? A Canadian example - Anna Johnston; A. John Sinclair; Robert B. Gibson (Environmental Impact Assessment Review, 2025)

Spatial unfolding of an extended La-140 source within a 0.5 km-wide exclusion zone using Compton gamma imaging measurements - N.J. Murtha; P.R.B. Saull; L.E. Sinclair; A.M.L. MacLeod; A. McCann (Journal of Environmental Radioactivity, 2025)

Recovery and Degradation Drive Changes in the Dispersal Capacity of Stream Macroinvertebrate Communities - Carlos Cano‐Barbacil; James S. Sinclair; Ellen A. R. Welti; Peter Haase (Global Change Biology, 2025)
Freshwater ecosystems face significant threats, including pollution, habitat loss, invasive species, and climate change. To address these challenges, management strategies and restoration efforts have been broadly implemented. Across Europe, such efforts have resulted in overall improvements in freshwater biodiversity, but recovery has stalled or failed to occur in many localities, which may be partly caused by the limited dispersal capacity of many species. Here, we used a comprehensive dataset comprising 1327 time series of freshwater macroinvertebrate communities ranging from 1968 to 2021 across 23 European countries to investigate whether dispersal capacity changes with the ecological quality of riverine systems. Sites experiencing improvements in ecological quality exhibited a net gain in species and tended to have macroinvertebrate communities containing species with stronger dispersal capacity (e.g., active aquatic and aerial dispersers, species with frequent propensity to drift, and insects with larger wings). In contrast, sites experiencing degradation of ecological quality exhibited a net loss of species and a reduction in the proportion of strong dispersers. However, this response varied extensively among countries and local sites, with some improving sites exhibiting no parallel gains in macroinvertebrates with higher dispersal capacity. Dispersal capacity of the local species pool can affect the success of freshwater ecosystem restoration projects. Management strategies should focus on enhancing landscape connectivity to create accessible “source” areas and refugia for sensitive taxa, especially as climate change reshapes habitat suitability. Additionally, biodiversity initiatives must incorporate adaptive decision‐making approaches that account for the site‐specific responses of macroinvertebrate communities to changes in ecological quality.

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Healing country together: A seagrass restoration case study from Gathaagudu (Shark Bay) - Elizabeth A. Sinclair; John Statton; Rachel Austin; Martin F. Breed; Richard Cross; Alex Dodd; Amrit Kendrick; Siegfried L. Krauss; Bianca McNeair; Nykita McNeair; Sean McNeair; Marika Oakley; et al. (Ocean & Coastal Management, 2024)

The ties that bind: how trees can enhance agroecological transitions - Marney E. Isaac; F. Sinclair; G. Laroche; A. Olivier; A. Thapa (Agroforestry Systems, 2024)
Agricultural systems have a long history of responding to various economic and socio-political forces, including supply and demand, political preferences and power inequalities. Our current food system continues to respond to contemporary forces with a call for sustainable transformations in the face of increased pressure and competition over resources, severe consequences of climatic change, widespread degradation of land and water resources, and the accelerating loss of biodiversity. Both agroforestry and agroecology have evolved as approaches to agricultural management that focus on the application of ecological principles to achieve sustainable agriculture. Agroecological principles are designed to engage with the entire agrifood system, for instance identifying broad participation and involving a diversity of actors and knowledge systems. Agroecological approaches to production have significant historical and contemporary links to agroforestry approaches, but not all agroecology involves trees and not all agroforestry is in line with agroecological principles. Drawing on (1) a literature review, (2) case studies on the agroforestry and agroecology nexus presented at the 5th World Congress on Agroforestry (WCA), and (3) audience responses to statements presented at the Congress, we explore the two main ways that agroforestry and agroecology come together: agroforestry that encompasses agroecological principles and agroecological transitions that involve trees. We review the status of agroecology, the functions specific to agroforestry that can enhance the achievement of agroecological outcomes, the tensions between simple agroforestry systems and agroecology, and the larger potential of multidimensional sustainability of agroforestry with the inclusion of agroecological principles. We also present the level of agreement on four key statements about the agroforestry-agroecology nexus enumerated at the WCA. It is clear that some features of agroforestry operationalize agroecological principles that aim to transition away from monocultures and the use of environmentally disruptive agrochemicals, and toward strengthening biodiversity and resilience. Yet, much remains to be done to enhance agroecological principles more fully in framing agroforestry practices and to incorporate trees within agroecological practices. Pathways to strengthen the nexus of agroforestry and agroecology are proposed, which focus on the role of trees in multifunctionality and resilience and using agroecological principles related to knowledge sharing and equity to enrich agroforestry practices.

A tomographic spatial-unfolding method for Compton gamma imaging measurements - N.J. Murtha; P.R.B. Saull; L.E. Sinclair; A.M.L. MacLeod; A. McCann (Journal of Environmental Radioactivity, 2024)

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Economic values for ecosystem services: A global synthesis and way forward - L.M. Brander; R. de Groot; J.P. Schägner; V. Guisado-Goñi; V. van 't Hoff; S. Solomonides; A. McVittie; F. Eppink; M. Sposato; L. Do; A. Ghermandi; M. Sinclair; et al. (Ecosystem Services, 2024)

Neonicotinoid mixture alters trophic interactions in a freshwater aquatic invertebrate community - Claire Duchet; Fan Hou; Cailin A. Sinclair; Zhenyu Tian; Alyssa Kraft; Vojtech Kolar; Edward P. Kolodziej; Jenifer K. McIntyre; John D. Stark (Science of The Total Environment, 2023)

Measuring Food Security among American Indian and Alaska Native Adults: Validity Evidence Supports the Use of the US Department of Agriculture Module - Cassandra J. Nguyen; Brian F. French; Tara L. Maudrie; Gary L. Ferguson; Valarie Blue Bird Jernigan; Ka`imi A. Sinclair (Journal of the Academy of Nutrition and Dietetics, 2023)

New life at old plants: Exploring solar power development at former nuclear power plant sites in the United States - Elisabeth Sinclair; Jim A. Hamilton (The Electricity Journal, 2023)

The imperative of arachidonic acid in early human development - Michael A. Crawford; Andrew J. Sinclair; Barbara Hall; Enitan Ogundipe; Yiqun Wang; Dimitrios Bitsanis; Ovrang B. Djahanbakhch; Laurence Harbige; Kebreab Ghebremeskel; Ivan Golfetto; Therishnee Moodley; Ahmed Hassam; et al. (Progress in Lipid Research, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Recent advances in the delivery and applications of nonviral CRISPR/Cas9 gene editing - Frazer Sinclair; Anjuman A. Begum; Charles C. Dai; Istvan Toth; Peter M. Moyle (Drug Delivery and Translational Research, 2023)

Saturn’s seasonal variability from four decades of ground-based mid-infrared observations - James S.D. Blake; L.N. Fletcher; G.S. Orton; A. Antuñano; M.T. Roman; Y. Kasaba; T. Fujiyoshi; H. Melin; D. Bardet; J.A. Sinclair; M. Es-Sayeh (Icarus, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

Is substrate choice an overlooked variable in ecotoxicology experiments? - Georgia M. Sinclair; Michela Di Giannantonio; Oliver A. H. Jones; Sara M. Long (Environmental Monitoring and Assessment, 2023)
It is crucial to understand the effects caused by experimental parameters such as temperature, light, and food type on lab and field-based ecotoxicology experiments, as these variables, and combinations thereof, can affect results. The type of substrate used in exposure experiments, however, is generally assumed to have no effect. This may not always be correct. The metabolic changes in the freshwater crustacean, Austrochiltonia subtenuis exposed to copper, using three common substrates, gauze; toilet paper; and cellulose were investigated. Substrate alone did not affect survival, but each substrate elicited a different metabolic response and adult and juvenile amphipods had different substrate preferences. Several classes of metabolites were shown to change in response to different substrates and toxicant. These included disaccharides, monosaccharides, fatty acids, and tricarboxylic acid cycle intermediates. The results illustrate that metabolomic responses can differ in response to experimental factors that were previously thought not to be significant. In fact, our data indicate that substrate should be viewed as an experimental factor as important to control for as more well-known confounders such as temperature or food, thus challenging the current paradigm. Assuming substrate type has no effect on the experiment could potentially lead to errors in contaminant toxicity assessments. We propose that ideal good practise would be that all experimental factors should be evaluated for their potential influence on metabolomic profiles prior to contaminant response experiments being undertaken.

Community-level responses to extreme flooding: the case of Brazilian Amazon ribeirinhos - Tiago Almudi; A. John Sinclair (Climate and Development, 2022)

The effects of nest location and beach environment on hatching success for leatherback (Dermochelys coriacea) and green (Chelonia mydas) sea turtles on Bioko Island, Equatorial Guinea - Callie A. Veelenturf; Elizabeth M. Sinclair; Peter Leopold; Frank V. Paladino; Shaya Honarvar (Marine Biology, 2022)

Dual effects of insulin resistance on mortality and function in non-diabetic older adults: findings from the Toledo Study of Healthy Aging - Leocadio Rodríguez-Mañas; Javier Angulo; José A. Carnicero; Mariam El Assar; Francisco J. García-García; Alan J. Sinclair (GeroScience, 2022)

Extreme hydroclimatic events in rural communities of the Brazilian Amazon: local perceptions of change, impacts, and adaptation - Tiago Almudi; A. John Sinclair (Regional Environmental Change, 2022)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Functional traits reveal the dominant drivers of long‐term community change across a North American Great Lake - James S. Sinclair; Michael E. Fraker; James M. Hood; Kenneth T. Frank; Mark R. DuFour; Ann Marie Gorman; Stuart A. Ludsin (Global Change Biology, 2021)
Ecosystems worldwide have been impacted by multiple anthropogenic stressors, yet efforts to understand and manage these impacts have been hindered by difficulties in disentangling relative stressor effects. Theoretically, the actions of individual stressors can be delineated based on associated changes in functional traits and these relationships should be generalizable across communities comprised of different species. Thus, combining trait perspectives with community composition data could help to identify the relative influence of different stressors. We evaluated the utility of this combined approach by quantifying shifts in fish species and trait composition in Lake Erie during the past 50 years (1969–2018) in relation to human‐driven changes in nutrient inputs, climate warming, and biological invasions. Species and trait shifts were also compared between two Lake Erie basins, which differ in their environmental and biological characteristics, to identify trait responses that were generalizable across different ecosystems versus those that were context dependent. Our analyses revealed consistent species changes across basins, and shifts in feeding and thermal traits, that were primarily associated with altered nutrient inputs (oligotrophication followed by eutrophication). We found no or inconsistent trait‐based evidence for the effects of warming and two invasive fishes. Context‐dependent trait responses were also evident; nutrient inputs were related to shifts in species tolerant of turbidity in the shallow, eutrophic western basin, which contrasted to shifts between benthopelagic and benthic species in the deeper central basin. Our results reveal the dominant effects of specific stressors on a large freshwater lake and offer a framework for combining species‐based and trait‐based approaches to delineate the impacts of simultaneous stressors on communities of perturbed natural ecosystems.

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Growth patterns of specialized reef fishes distributed across the Red Sea to Gulf of Aden - Joseph D. DiBattista; Brett M. Taylor; Jean-Paul A. Hobbs; Tane H. Sinclair-Taylor; Darren J. Coker; Elizabeth D. L. Trip; J. Howard Choat; Diego Lozano-Cortés; Nora M. Kandler; Michael L. Berumen (Environmental Biology of Fishes, 2021)

“Two-Row” cross-cultural learning for collaborative governance of forestland in northwestern Ontario, Canada - Melanie Zurba; A. John Sinclair; Alan P. Diduck (Regional Environmental Change, 2021)

Climate change adaptation in and through agroforestry: four decades of research initiated by Peter Huxley - Meine van Noordwijk; Richard Coe; Fergus L. Sinclair; Eike Luedeling; Jules Bayala; Catherine W. Muthuri; Peter Cooper; Roeland Kindt; Lalisa Duguma; Christine Lamanna; Peter A. Minang (Mitigation and Adaptation Strategies for Global Change, 2021)
Agroforestry (AF)-based adaptation to global climate change can consist of (1) reversal of negative trends in diverse tree cover as generic portfolio risk management strategy; (2) targeted, strategic, shift in resource capture (e.g. light, water) to adjust to changing conditions (e.g. lower or more variable rainfall, higher temperatures); (3) vegetation-based influences on rainfall patterns; or (4) adaptive, tactical, management of tree-crop interactions based on weather forecasts for the (next) growing season. Forty years ago, a tree physiological research tradition in aboveground and belowground resource capture was established with questions and methods on climate-tree-soil-crop interactions in space and time that are still relevant for today’s challenges. After summarising early research contributions, we review recent literature to assess current levels of uncertainty in climate adaptation assessments in and through AF. Quantification of microclimate within and around tree canopies showed a gap between standard climate station data (designed to avoid tree influences) and the actual climate in which crop and tree meristems or livestock operates in real-world AF. Where global scenario modelling of ‘macroclimate’ change in mean annual rainfall and temperature extrapolates from climate station conditions in past decades, it ignores microclimate effects of trees. There still is a shortage of long-term phenology records to analyse tree biological responses across a wide range of species to climate variability, especially where flowering and pollination matter. Physiological understanding can complement farmer knowledge and help guide policy decisions that allow AF solutions to emerge and tree germplasm to be adjusted for the growing conditions expected over the lifetime of a tree.

Myocardial Perfusion Simulation for Coronary Artery Disease: A Coupled Patient-Specific Multiscale Model - Lazaros Papamanolis; Hyun Jin Kim; Clara Jaquet; Matthew Sinclair; Michiel Schaap; Ibrahim Danad; Pepijn van Diemen; Paul Knaapen; Laurent Najman; Hugues Talbot; Charles A. Taylor; Irene Vignon-Clementel (Annals of Biomedical Engineering, 2021)
Patient-specific models of blood flow are being used clinically to diagnose and plan treatment for coronary artery disease. A remaining challenge is bridging scales from flow in arteries to the micro-circulation supplying the myocardium. Previously proposed models are descriptive rather than predictive and have not been applied to human data. The goal here is to develop a multiscale patient-specific model enabling blood flow simulation from large coronary arteries to myocardial tissue. Patient vasculatures are segmented from coronary computed tomography angiography data and extended from the image-based model down to the arteriole level using a space-filling forest of synthetic trees. Blood flow is modeled by coupling a 1D model of the coronary arteries to a single-compartment Darcy myocardium model. Simulated results on five patients with non-obstructive coronary artery disease compare overall well to [ $$^{15}$$ 15 O] $$\text {H}_{{2}}$$ H 2 O PET exam data for both resting and hyperemic conditions. Results on a patient with severe obstructive disease link coronary artery narrowing with impaired myocardial blood flow, demonstrating the model’s ability to predict myocardial regions with perfusion deficit. This is the first report of a computational model for simulating blood flow from the epicardial coronary arteries to the left ventricle myocardium applied to and validated on human data.

Consistent and transient drivers of freshwater zooplankton communities - James S. Sinclair; Shelley E. Arnott; William A. Nelson; Kaitlyn B. Brougham (Journal of Biogeography, 2021)
Aim Inferences of the predominant processes that structure communities are commonly based on single ‘snapshots’ in time, which may miss temporally transient but important mechanisms. In this study, we compared key environmental and spatial drivers of zooplankton composition across multiple years to quantify shifts in their relative importance through time, and to identify any drivers of temporal change. Location Southern Ontario, Canada. Taxon Zooplankton. Methods Zooplankton were collected from 29 lakes in southern Ontario, Canada over four years (2013–2016). Variation partitioning was used to quantify the relative importance of independent and covarying components of local environmental conditions, regional east‐west and north‐south compositional trends, and inter‐lake geographic distance in each year. Measured environmental metrics included aspects of lake morphology and chemistry, and spatial relationships were quantified using lake latitude/longitude coordinates and Moran's Eigenvector Maps (MEMs). Redundancy analyses (RDAs) were also used to compare the influence of individual environmental and spatial variables across years. Results Most local‐scale and regional‐scale community processes were consistently important across all surveyed years, but some were less consistent. Specifically, geomorphology was always an important driver of local environmental and regional spatial community patterns. This occurred because local community composition was strongly affected by whether a lake was shallower versus deeper, and due to spatial clusters of shallow and deep lakes that produced negative spatial autocorrelation in community composition. Conversely, the individual influences of lake chemistry and spatial east‐west compositional trends were important in some years and not in others, potentially due to inter‐annual shifts in the predominant environmental variables and extreme weather events. Main conclusions A single‐year community snapshot can provide insight into consistent or slowly changing community structuring processes, such as those driven by geomorphology, but may not completely capture temporally transient mechanisms. Furthermore, snapshots collected during anomalous seasons or years may misrepresent which mechanisms are predominantly determining community composition. Future efforts to understand local and regional community drivers would therefore benefit from considering which processes are likely temporally ‘consistent’ versus ‘transient’, and studies with more variable components would benefit from considering or controlling for temporal shifts in their importance.

Climatology, variability, and trends in near‐surface wind speeds over the North Atlantic and Europe during 1979–2018 based on ERA5 - Terhi K. Laurila; Victoria A. Sinclair; Hilppa Gregow (International Journal of Climatology, 2021)
This study presents the monthly 10‐m wind speed climatology, decadal variability and possible trends in the North Atlantic and Europe from ERA5 reanalysis from 1979 to 2018 and investigates the physical reasons for the decadal variability. Additionally, temporal time series are examined in three locations: the central North Atlantic, Finland and Iberian Peninsula. The 40‐year mean and the 98th percentile wind speeds emphasize a distinct land‐sea contrast and a seasonal variation with the strongest winds over the ocean and during winter. The strongest winds and the highest variability are associated with the storm tracks and local wind phenomena such as the mistral. The extremeness of the winds is examined with an extreme wind factor (the 98th percentile divided by mean wind speeds) which in all months is higher in southern Europe than in northern Europe. Mostly no linear trends in 10‐m wind speeds are identified in the three locations but large annual and decadal variability is evident. The decadal 10‐m wind speeds were stronger than average in the 1990s in northern Europe and in the 1980s and 2010s in southern Europe. These decadal changes were largely explained by the positioning of the jet stream and storm tracks and the strength of the north–south pressure gradient in the North Atlantic. The 10‐m winds have a positive correlation with the North Atlantic Oscillation in the central North Atlantic and Finland on annual scales and during cold season months and a negative correlation in Iberian Peninsula mostly from July to March. The Atlantic Multi‐decadal Oscillation has a moderate negative correlation with the winds in the central North Atlantic but no correlation in Finland and Iberian Peninsula. Overall, our results emphasize that while linear trends in wind speeds may show a general long‐term trend, more information on the changes is obtained by analysing long‐term variability.

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Blue Restoration – Building Confidence and Overcoming Barriers - Phoebe J. Stewart-Sinclair; Jemma Purandare; Elisa Bayraktarov; Nathan Waltham; Simon Reeves; John Statton; Elizabeth A. Sinclair; Benjamin M. Brown; Zoë I. Shribman; Catherine E. Lovelock (Frontiers in Marine Science, 2020)

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Process Monitoring of Moisture Content and Mass Transfer Rate in a Fluidised Bed with a Low Cost Inline MEMS NIR Sensor - Claudio R. Avila; Joan Ferré; Rodrigo Rocha de Oliveira; Anna de Juan; Wayne E. Sinclair; Faiz M. Mahdi; Ali Hassanpour; Timothy N. Hunter; Richard A. Bourne; Frans L. Muller (Pharmaceutical Research, 2020)
Purpose The current trend for continuous drug product manufacturing requires new, affordable process analytical techniques (PAT) to ensure control of processing. This work evaluates whether property models based on spectral data from recent Fabry–Pérot Interferometer based NIR sensors can generate a high-resolution moisture signal suitable for process control. Methods Spectral data and offline moisture content were recorded for 14 fluid bed dryer batches of pharmaceutical granules. A PLS moisture model was constructed resulting in a high resolution moisture signal, used to demonstrate (i) endpoint determination and (ii) evaluation of mass transfer performance. Results The sensors appear robust with respect to vibration and ambient temperature changes, and the accuracy of water content predictions (±13 % ) is similar to those reported for high specification NIR sensors. Fusion of temperature and moisture content signal allowed monitoring of water transport rates in the fluidised bed and highlighted the importance water transport within the solid phase at low moisture levels. The NIR data was also successfully used with PCA-based MSPC models for endpoint detection. Conclusions The spectral quality of the small form factor NIR sensor and its robustness is clearly sufficient for the construction and application of PLS models as well as PCA-based MSPC moisture models. The resulting high resolution moisture content signal was successfully used for endpoint detection and monitoring the mass transfer rate.

Regenerated trees in farmers’ fields increase soil carbon across the Sahel - J. Bayala; J. Sanou; H. R. Bazié; R. Coe; A. Kalinganire; F. L. Sinclair (Agroforestry Systems, 2020)

Practical actions for applied systematic conservation planning - Emily A. Botts; Genevieve Pence; Stephen Holness; Kerry Sink; Andrew Skowno; Amanda Driver; Linda R. Harris; Philip Desmet; Boyd Escott; Mervyn Lötter; Jeanne Nel; Tammy Smith; et al. (Conservation Biology, 2019)
Systematic conservation planning is intended to inform spatially explicit decision making. Doing so requires that it be integrated into complex regulatory and governance processes, and there are limited instances where this has been achieved effectively. South Africa is a global leader in the application of conservation plans, the outputs of which are widely used for spatial planning and decision making in many spheres of government. We aimed to determine how conservation planning in the country progressed from theory to implementation, and to identify practical actions that enabled this transition, by assessing temporal trends in the characteristics of conservation plans (1990–2017, n = 94). Since 2010 conservation planning has entered an operational period characterized by government leadership of plans, administrative rather than ecological planning domains, decreasing size of planning units, increasing emphasis on end‐user products, and scheduled revision of plans. Key actions that enabled this progression include transitioning leadership of plans from scientists to practitioners, building capacity within implementing agencies, creating opportunities to integrate plans in legislative processes, establishing a strong community of practice, adopting implementation‐focused methods, and balancing standardization with innovation. Learning from this model will allow other countries, particularly those with a similar megadiverse, developing context, to operationalize conservation planning into spatial planning and decision making.

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Wide outcrossing provides functional connectivity for new and old Banksia populations within a fragmented landscape - Alison L. Ritchie; Rodney J. Dyer; Paul G. Nevill; Elizabeth A. Sinclair; Siegfried L. Krauss (Oecologia, 2019)

Sensitivity of idealised baroclinic waves to mean atmospheric temperature and meridional temperature gradient changes - Mika Rantanen; Jouni Räisänen; Victoria A. Sinclair; Heikki Järvinen (Climate Dynamics, 2019)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

The limitations of some European healthcare databases for monitoring the effectiveness of pregnancy prevention programmes as risk minimisation measures - R. A. Charlton; V. Bettoli; H. J. Bos; A. Engeland; E. Garne; R. Gini; A. V. Hansen; L. T. W. de Jong-van den berg; S. Jordan; K. Klungsøyr; A. J. Neville; A. Pierini; et al. (European Journal of Clinical Pharmacology, 2018)

Breakdown in assortative mating leads to hybrid swarm in pygmy angelfishes - J. P. A. Hobbs; J. D. DiBattista; T. H. Sinclair-Taylor (Coral Reefs, 2018)

Heat waves in Finland: present and projected summertime extreme temperatures and their associated circulation patterns - Sol Kim; Victoria A. Sinclair; Jouni Räisänen; Reija Ruuhela (International Journal of Climatology, 2018)
The number and intensity of individual hot days affecting Finland in the current and future climate is investigated together with the circulation patterns associated with the hot days. In addition, the number, length and intensity of heat waves lasting at least 3 days is also considered. ERA‐Interim reanalysis data and both direct model output and bias‐corrected data for historical and future climate [representative concentration pathway 4.5 (RCP4.5) scenario] simulations from 17 global climate models are analysed. Three intensities of heat waves and hot days are defined based on daily mean temperature thresholds of 20, 24 and 28 °C. The percentage of summertime days which exceed these temperature thresholds is shown to increase in the future. In ERA‐Interim, 24% of summertime days in southern Finland exceed the lowest temperature threshold while none exceed the highest temperature threshold. Under the RCP4.5 scenario these values increase to 47 and 1%, respectively. Larger relative changes occur in northern Finland. Heat waves are also longer in the RCP4.5 simulations than in the historical simulations. In southern Finland, the mean length of a heat wave where the 20 °C daily mean temperature is exceeded is 6.1 days in the historical simulations but increases to 9.4 days in the RCP4.5 simulations. The hot days in both northern and southern Finland are associated with a statistically significant positive pressure anomaly over Finland and to the east to Finland and a statistically significant negative pressure anomaly over Russia between 90 and 120°E. These pressure anomalies were evident for all intensities of hot days in the current climate and the future climate. The magnitude of the pressure anomalies increases as the daily mean temperature threshold increases. However, for hot days which exceed the same daily mean temperature threshold, the pressure anomalies are weaker in the RCP4.5 simulations than in the historical or ERA‐Interim data.

Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control - Laura J. Wilson; Emma Cockburn; Katherine Paice; Scott Sinclair; Tanwir Faki; Frank A. Hills; Marcela B. Gondek; Alyssa Wood; Lygeri Dimitriou (European Journal of Applied Physiology, 2018)

Water–fat MRI in a hibernator reveals seasonal growth of white and brown adipose tissue without cold exposure - Amanda MacCannell; Kevin Sinclair; Lannette Friesen-Waldner; Charles A. McKenzie; James F. Staples (Journal of Comparative Physiology B, 2017)

Comparative phylogeography of reef fishes from the Gulf of Aden to the Arabian Sea reveals two cryptic lineages - Joseph D. DiBattista; Michelle R. Gaither; Jean-Paul A. Hobbs; Pablo Saenz-Agudelo; Marek J. Piatek; Brian W. Bowen; Luiz A. Rocha; J. Howard Choat; Jennifer H. McIlwain; Mark A. Priest; Tane H. Sinclair-Taylor; Michael L. Berumen (Coral Reefs, 2017)

Mutations in KIAA0753 cause Joubert syndrome associated with growth hormone deficiency - Joshi Stephen; Thierry Vilboux; Luhe Mian; Chulaluck Kuptanon; Courtney M. Sinclair; Deniz Yildirimli; Dawn M. Maynard; Joy Bryant; Roxanne Fischer; Meghana Vemulapalli; James C. Mullikin; Marjan Huizing; et al. (Human Genetics, 2017)

Hybridisation among groupers (genus Cephalopholis) at the eastern Indian Ocean suture zone: taxonomic and evolutionary implications - Samuel D. Payet; Jean-Paul A. Hobbs; Joseph D. DiBattista; Stephen J. Newman; Tane Sinclair-Taylor; Michael L. Berumen; Jennifer L. McIlwain (Coral Reefs, 2016)

Genetic signatures of Bassian glacial refugia and contemporary connectivity in a marine foundation species - Elizabeth A. Sinclair; Janet M. Anthony; Dougal Greer; Leonardo Ruiz‐Montoya; Suzanna M. Evans; Siegfried L. Krauss; Gary A. Kendrick (Journal of Biogeography, 2016)
Aim To examine the population genetic structure in Posidonia australis meadows , a marine foundation species capable of long distance dispersal ( LDD ), and the role of historical versus contemporary processes in shaping post Last Glacial Maximum ( LGM ) re‐colonization. Location Southeastern Australia including the Bass Strait Islands. Methods We generated multilocus genotypes and assessed spatial patterns of genetic diversity. Relationships among meadows were assessed in terms of historical sea level changes, oceanic boundary currents and contemporary seed dispersal based on a hydrodynamic model. Results There was strong regional spatial genetic structuring among P. australis meadows in south‐eastern Australia, which was congruent with three recognized marine biogeographical provinces [Peronian (eastern), Flindersian (western and southern), and Maugean (south‐eastern)]. The genetic data suggest Maugean meadows persisted in isolation during the LGM , with evidence for admixture and contemporary gene flow. Simulated dispersal events identified high rates of local and regional demographic connectivity, with evidence for occasional LDD events. Main conclusions The strong regional differentiation is consistent with long‐term barriers to dispersal persisting in the marine environment through many sea level fluctuations. Bass Strait Island meadows all have strong signals of genetic admixture. A weak but significant isolation by distance relationship is consistent with a historical signal and contemporary seed dispersal mostly within the Bass Strait.

Can we predict ectotherm responses to climate change using thermal performance curves and body temperatures? - Brent J. Sinclair; Katie E. Marshall; Mary A. Sewell; Danielle L. Levesque; Christopher S. Willett; Stine Slotsbo; Yunwei Dong; Christopher D. G. Harley; David J. Marshall; Brian S. Helmuth; Raymond B. Huey (Ecology Letters, 2016)
Thermal performance curves ( TPC s), which quantify how an ectotherm's body temperature ( T b ) affects its performance or fitness, are often used in an attempt to predict organismal responses to climate change. Here, we examine the key – but often biologically unreasonable – assumptions underlying this approach; for example, that physiology and thermal regimes are invariant over ontogeny, space and time, and also that TPC s are independent of previously experienced T b. We show how a critical consideration of these assumptions can lead to biologically useful hypotheses and experimental designs. For example, rather than assuming that TPC s are fixed during ontogeny, one can measure TPC s for each major life stage and incorporate these into stage‐specific ecological models to reveal the life stage most likely to be vulnerable to climate change. Our overall goal is to explicitly examine the assumptions underlying the integration of TPC s with T b , to develop a framework within which empiricists can place their work within these limitations, and to facilitate the application of thermal physiology to understanding the biological implications of climate change.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Learning Through New Approaches to Forest Governance: Evidence from Harrop-Procter Community Forest, Canada - Felicitas Egunyu; Maureen G. Reed; John A. Sinclair (Environmental Management, 2016)

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Effects of substrate size and cleaning regime on growth and survival of captive-bred juvenile freshwater pearl mussels, Margaritifera margaritifera (Linnaeus, 1758) - Louise Lavictoire; Evelyn Moorkens; Andrew D. Ramsey; William Sinclair; Roger A. Sweeting (Hydrobiologia, 2016)

Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al. - Elizabeth A. Sinclair; Renae Hovey; John Statton; Matthew W. Fraser; Marion L. Cambridge; Gary A. Kendrick (Estuaries and Coasts, 2016)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

When biogeographical provinces collide: hybridization of reef fishes at the crossroads of marine biogeographical provinces in the Arabian Sea - Joseph D. DiBattista; Luiz A. Rocha; Jean‐Paul A. Hobbs; Song He; Mark A. Priest; Tane H. Sinclair‐Taylor; Brian W. Bowen; Michael L. Berumen (Journal of Biogeography, 2015)
Aim Suture zones are areas where closely related species from different biogeographical regions come into contact and interbreed. This concept originated from the study of terrestrial ecosystems but it remains unclear whether a similar phenomenon occurs in the marine environment. Here we investigate a potential suture zone from a previously unknown hybrid hotspot at the Socotra Archipelago (Yemen), located in the Arabian Sea, where fauna from the Red Sea, Gulf of Aden, Arabian Sea, western Indian Ocean and greater Indo‐Polynesian Province intersect. Location Red Sea, Gulf of Aden, Arabian Sea and Indian Ocean. Methods Putative hybrid reef fish were identified based on intermediate coloration and morphology. Underwater observations and collections were conducted to determine: (1) whether parent species form heterospecific social groups or breeding pairs; (2) the sex and reproductive status of morphologically intermediate individuals; and (3) whether parent species were forming mixed species associations owing to a dearth of conspecific partners. To support hybrid status, morphologically intermediate and parental individuals were genotyped using mitochondrial DNA cytochrome c oxidase subunit I ( COI ), nuclear recombination‐activating gene 2 ( RAG 2 ) and the nuclear TMO ‐4C4 (TMO) gene. Results We observed putative hybrids involving 14 species from four reef fish families at Socotra. Most cases involved a parental species with a restricted distribution (e.g. Red Sea or Arabian Sea) and a broadly distributed Indo‐Pacific species. In most cases, at least one of the parent species was rare at Socotra. Hybrid gene flow was largely unidirectional, and although introgression was rare, we found evidence that some butterflyfish and surgeonfish hybrids were fertile and formed breeding groups with parental species. Main conclusions The rate of hybrid discovery at Socotra is much greater than that recorded elsewhere in the marine environment and involved both allopatric and sympatric species. This study highlights the importance of biogeographical location, reef habitat, environmental conditions and abundance disparities at Socotra in potentially facilitating hybridization among reef fishes at the edge of their distribution.

The genetic structure of Nautilus pompilius populations surrounding Australia and the Philippines - Rachel C. Williams; Benjamin C. Jackson; Ludovic Duvaux; Deborah A. Dawson; Terry Burke; William Sinclair (Molecular Ecology, 2015)
Understanding the distribution of genetic diversity in exploited species is fundamental to successful conservation. Genetic structure and the degree of gene flow among populations must be assessed to design appropriate strategies to prevent the loss of distinct populations. The cephalopod Nautilus pompilius is fished unsustainably in the Philippines for the ornamental shell trade and has limited legislative protection, despite the species' recent dramatic decline in the region. Here, we use 14 microsatellite markers to evaluate the population structure of N. pompilius around Australia and the Philippines. Despite their relative geographical proximity, Great Barrier Reef individuals are genetically isolated from Osprey Reef and Shark Reef in the Coral Sea ( F ST = 0.312, 0.229, respectively). Conversely, despite the larger geographical distances between the Philippines and west Australian reefs, samples display a small degree of genetic structure ( F ST = 0.015). Demographic scenarios modelled using approximate Bayesian computation analysis indicate that this limited divergence is not due to contemporary gene flow between the Philippines and west Australia. Instead, present‐day genetic similarity can be explained by very limited genetic drift that has occurred due to large average effective population sizes that persisted at both locations following their separation. The lack of connectivity among populations suggests that immigrants from west Australia would not facilitate natural recolonization if Philippine populations were fished to extinction. These data help to rectify the paucity of information on the species' biology currently inhibiting their conservation classification. Understanding population structure can allow us to facilitate sustainable harvesting, thereby preserving the diversity of genetically distinct stocks.

Isolation and characterisation of microsatellite loci for the ancient cephalopod, Nautilus pompilius - Rachel C. Williams; Deborah A. Dawson; Gavin J. Horsburgh; William Sinclair (Conservation Genetics Resources, 2015)

Learning for Sustainability Among Faith-Based Organizations in Kenya - Joanne M. Moyer; A. John Sinclair; Alan P. Diduck (Environmental Management, 2014)

Loss of microbial diversity in soils is coincident with reductions in some specialized functions - Brajesh K. Singh; Christopher Quince; Catriona A. Macdonald; Amit Khachane; Nadine Thomas; Waleed Abu Al‐Soud; Søren J. Sørensen; Zhili He; Duncan White; Alex Sinclair; Bill Crooks; Jizhong Zhou; et al. (Environmental Microbiology, 2014)
Summary Loss of microbial diversity is considered a major threat because of its importance for ecosystem functions, but there is a lack of conclusive evidence that diversity itself is reduced under anthropogenic stress, and about the consequences of diversity loss. Heavy metals are one of the largest, widespread pollutant types globally, and these represent a significant environmental stressor for terrestrial microbial communities. Using combined metagenomics and functional assays, we show that the compositional and functional response of microbial communities to long‐term heavy metal stress results in a significant loss of diversity. Our results indicate that even at a moderate loss of diversity, some key specialized functions (carried out by specific groups) may be compromised. Together with previous work, our data suggest disproportionate impact of contamination on microbes that carry out specialized, but essential, ecosystem functions. Based on these findings, we propose a conceptual framework to explicitly consider diversity of functions and microbial functional groups to test the relationship between biodiversity and soil functions.

Genetic diversity in threatened Posidonia australis seagrass meadows - Suzanna M. Evans; Elizabeth A. Sinclair; Alistair G. B. Poore; Peter D. Steinberg; Gary A. Kendrick; Adriana Vergés (Conservation Genetics, 2014)

Multi-Scale Parameterisation of a Myocardial Perfusion Model Using Whole-Organ Arterial Networks - Eoin R. Hyde; Andrew N. Cookson; Jack Lee; Christian Michler; Ayush Goyal; Taha Sochi; Radomir Chabiniok; Matthew Sinclair; David A. Nordsletten; Jos Spaan; Jeroen P. H. M. van den Wijngaard; Maria Siebes; et al. (Annals of Biomedical Engineering, 2014)

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

Site-specific water quality guidelines: 2. Development of a water quality regulation framework for pulse exposures of mine water discharges at a uranium mine in northern Australia - A. Sinclair; K. Tayler; R. van Dam; A. Hogan (Environmental Science and Pollution Research, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Neuronal sirtuin1 mediates retinal vascular regeneration in oxygen-induced ischemic retinopathy - Jing Chen; Shaday Michan; Aimee M. Juan; Christian G. Hurst; Colman J. Hatton; Dorothy T. Pei; Jean-Sebastien Joyal; Lucy P. Evans; Zhenghao Cui; Andreas Stahl; Przemyslaw Sapieha; David A. Sinclair; et al. (Angiogenesis, 2013)

Contrasting effects of manure and green waste biochars on the properties of an acidic ferralsol and productivity of a subtropical pasture - P. G. Slavich; K. Sinclair; S. G. Morris; S. W. L. Kimber; A. Downie; L. Van Zwieten (Plant and Soil, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Ontogenetic variation in cold tolerance plasticity in Drosophila: is the Bogert effect bogus? - Katherine A. Mitchell; Brent J. Sinclair; John S. Terblanche (The Science of Nature, 2013)

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Identification of QTLs associated with limited leaf hydraulic conductance in soybean - V. Carpentieri-Pipolo; A. E. Pipolo; H. Abdel-Haleem; H. R. Boerma; T. R. Sinclair (Euphytica, 2012)

Identification of calanoid copepod prey species via molecular detection of carbon fixation genes - Wilford B. Boling; Geoff A. Sinclair; Boris Wawrik (Marine Biology, 2012)

Morphological and AFLP diversity in Thaumatococcus daniellii, the source of the protein sweetener thaumatin - Wojciech S. Waliszewski; Fergus L. Sinclair; Katherine A. Steele (Genetic Resources and Crop Evolution, 2012)

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 2. An Evaluation of the Predictive Ability of Effects-Based Sediment-Quality Guidelines - Donald D. MacDonald; Christopher G. Ingersoll; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Ning Wang; Corrine Severn; Ron Gouguet; John Meyer; Jay Field (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Otolith size and location in digestive tracts of northern fur seals ( Callorhinus ursinus ): Implications for dietary interpretations - E. H. Sinclair; A. E. York; G. A. Antonelis (Marine Mammal Science, 2011)
Walleye pollock ( Theragra chalcogramma ) otoliths ( n = 2,706) recovered from stomachs, small intestines, and colons of 43 northern fur seals ( Callorhinus ursinus ) were evaluated for size and wear by location in the digestive tract. Pollock fork length was regressed on otolith length after correction for erosion, and age was estimated from the calculated body size. Age‐1+ pollock otoliths (≥6.3‐mm length) were concentrated in stomachs while age‐0 otoliths (≤6.2‐mm length) were concentrated in colons. Less than 10% of otoliths were found in the small intestines. Pollock age decreased with progression along seal gastrointestinal tracts. Otolith quality increased along gastrointestinal tracts in numbers ≥20, which was typical of age‐0 otoliths recovered from colons. Otolith distribution by age and quality along gastrointestinal tracts suggests that small (≤12 cm) schooling prey are consumed in large volume and passed as a bolus rapidly through the digestive tract before significant erosion of bony remains occurs; while larger prey are eaten in smaller volume and subjected to otolith erosion due to longer retention in the stomach. Our results illustrate the importance of multiple sampling strategies to comprehensively represent prey size in pinniped diet.

Mass schooling and mortality of Canthigaster bennetti in Sulawesi - A. L. Vail; T. Sinclair-Taylor (Coral Reefs, 2011)

The effect of land use systems on tree diversity: farmer preference and species composition of cocoa-based agroecosystems in Ghana - Luke C. N. Anglaaere; Joseph Cobbina; Fergus L. Sinclair; Morag A. McDonald (Agroforestry Systems, 2011)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Potential root depth development and nitrogen uptake by tetraploid bahiagrass hybrids - Carlos A. Acuña; Thomas R. Sinclair; Cheryl L. Mackowiak; Ann R. Blount; Kenneth H. Quesenberry; Wayne W. Hanna (Plant and Soil, 2010)

Characterisation of polymorphic microsatellite markers isolated from Drakaea glyptodon Fitz. (Orchidaceae) - J. M. Anthony; R. D. Phillips; E. A. Sinclair; K. W. Dixon (Conservation Genetics Resources, 2010)

Ecological specialization in mycorrhizal symbiosis leads to rarity in an endangered orchid - NIGEL D. SWARTS; ELIZABETH A. SINCLAIR; ANTHONY FRANCIS; KINGSLEY W. DIXON (Molecular Ecology, 2010)

Synoptic Controls on Boundary-Layer Characteristics - Victoria A. Sinclair; Stephen E. Belcher; Suzanne L. Gray (Boundary-Layer Meteorology, 2010)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

Genetic diversity in fragmented populations of the critically endangered spider orchid Caladenia huegelii: implications for conservation - Nigel D. Swarts; Elizabeth A. Sinclair; Siegfried L. Krauss; Kingsley W. Dixon (Conservation Genetics, 2009)

A 3D modeling method to calculate the surface areas of coral branches - A. M. Jones; N. E. Cantin; R. Berkelmans; B. Sinclair; A. P. Negri (Coral Reefs, 2008)

Losing ‘Nemo’: bleaching and collection appear to reduce inshore populations of anemonefishes - A. M. Jones; S. Gardner; W. Sinclair (Journal of Fish Biology, 2008)
Surveys of anemonefishes (Amphiprioninae) were conducted on reefs in two regions of the Great Barrier Reef Marine Park with contrasting histories of disturbance to determine the degree to which spatial variation might be explained by bleaching or management status. Densities of anemonefishes were lower on reefs in the bleaching‐impacted Keppel Islands than on reefs in Far North Queensland. No anemonefishes or anemones were found on or near bleached corals in the Keppel Islands. Furthermore, the highest densities of fishes were found on reefs closed to fishing and aquarium collecting in both the Keppel Islands and Far North Queensland, which suggests that collecting is compounding the effects of bleaching. These results emphasize the importance of understanding the interaction between bleaching events and anthropogenic disturbance upon commercially exploited species.

Environmental Impact Assessment Under the Mackenzie Valley Resource Management Act: Deliberative Democracy in Canada’s North? - Patricia Fitzpatrick; A. John Sinclair; Bruce Mitchell (Environmental Management, 2008)

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Do Exotic Vertebrates Structure the Biota of Australia? An Experimental Test in New South Wales - C. Davey; A. R. E. Sinclair; R. P. Pech; A. D. Arthur; C. J. Krebs; A. E. Newsome; D. Hik; R. Molsher; K. Allcock (Ecosystems, 2006)

Diversity of Glomale Mycorrhizal Fungi in Maize/Sesbania Intercrops and Maize Monocrop Systems in Southern Malawi - Joyce M. Jefwa; Robert Sinclair; Jumanne A. Maghembe (Agroforestry Systems, 2006)

Do patterns of Steller sea lion ( Eumetopias jubatus ) diet, population trend and cetacean occurrence reflect oceanographic domains from the Alaska Peninsula to the central Aleutian Islands? - ELIZABETH H. SINCLAIR; SUE E. MOORE; NANCY A. FRIDAY; TONYA K. ZEPPELIN; JANICE M. WAITE (Fisheries Oceanography, 2005)
Shipboard surveys were conducted along the Aleutian Islands in 2001 and 2002 to assess the influence of a suite of biophysical parameters on regional patterns in the distribution of cetaceans and Steller sea lions (SSL; Eumetopias jubatus ). Distributions of four large whale species: fin ( Balaenoptera physalus ), humpback ( Megaptera novaeangliae ), minke ( B. acutorostrata ) and sperm ( Physeter macrocephalus ) aligned with proposed metapopulation breaks in diet and population trend of SSLs. Dall's porpoise ( Phocoenoides dalli ) and killer whales ( Orcinus orca ) were widely distributed throughout the study area, and killer whales were particularly prevalent along the north Aleutian Island coastlines between Unimak Pass and Samalga Pass. Biopsies determined that most killer whales (92%) were of the piscivorous (resident) ecotype as opposed to the mammal‐eating (transient) ecotype observed in 2002 only. Generalized additive models (GAMs) were used to explore relationships between these multispecies patterns in distribution, oceanographic variables (salinity, temperature, fluorescence and depth) and proximity to six Aleutian passes. The GAMs indicated the best‐fit models and most significant correlations as determined by the Akaike function and Cp‐statistics were: depth and proximity to the nearest measured pass for SSLs and all cetaceans, respectively; frequencies of herring and salmon in SSL diet with population trend; fluorescence in the top 50 m with occurrence of humpback, minke, and killer whales; and surface temperature with occurrence of humpback, killer, and sperm whales. Results of the GAM analyses suggest foci for future investigation of relationships between physical variables and interspecific patterns of marine mammal distribution.

Regulation of Harvest-induced Senescence in Broccoli (Brassica oleracea var. italica) by Cytokinin, Ethylene, and Sucrose - Nigel E. Gapper; Simon A. Coupe; Marian J. McKenzie; Ben K. Sinclair; Ross E. Lill; Paula E. Jameson (Journal of Plant Growth Regulation, 2005)

Incorporating an environmental stock–recruitment relationship in the assessment of Pacific cod ( Gadus macrocephalus ) - A. F. SINCLAIR; W. R. CRAWFORD (Fisheries Oceanography, 2005)
The robustness of a previously described environmentally mediated stock–recruitment relationship for Pacific cod in Hecate Strait, BC, Canada was tested with 10 yr of additional data. The original analysis tested several alternative hypotheses and concluded that water transport through Hecate Strait, as indicated by sea level height, coupled with cod spawning biomass formed the best model. The present analysis indicates the relationship held through the 1990s. The implications of variation in sea level on stock production were investigated with a delay‐difference stock production model that included an environmentally mediated stock–recruitment relationship. The model predicted that the maximum fishery yield would vary between 1750 and 3670 t yr −1 over the observed range of sea level height, and the estimated unsustainable fishing mortality during periods of low productivity would be only 0.5 times that in periods of high productivity.

Landscape scale, heterogeneity, and the viability of Serengeti grazers - John M. Fryxell; John F. Wilmshurst; Anthony R. E. Sinclair; Daniel T. Haydon; Robert D. Holt; Peter A. Abrams (Ecology Letters, 2005)
Species persistence can be threatened by substantial temporal variation in food resources over time. On the other hand, spatial heterogeneity in resources at the landscape scale might allow mobile consumers to compensate for temporal variability in resource availability at the local scale. We evaluated this hypothesis, using an extensive data set on foraging, grass growth, and movement by Thomson's gazelles living on the Serengeti Plains. Here we show that modelled populations of Thomson's gazelles can only persist under Serengeti conditions in the face of observed levels of rainfall stochasticity by making adaptive movements to take advantage of ephemeral spatial distributions of food resources. More importantly, our models suggest that Thomson's gazelles in Serengeti require unrestricted access to relatively large areas of grassland (> 1600 km 2 ) to guarantee long‐term persistence, particularly when there is positive spatial autocorrelation in resource abundance, as is the case in Serengeti. If this proves to be true for other species and/or other systems, then understanding of complex behavioural responses to spatially and temporally heterogeneous food supplies may be essential to successful conservation of grazing herbivores.

RETROSPECTIVE ISOTOPIC ANALYSES OF STELLER SEA LION TOOTH ANNULI AND SEABIRD FEATHERS: A CROSS‐TAXA APPROACH TO INVESTIGATING REGIME AND DIETARY SHIFTS IN THE GULF OF ALASKA - Keith A. Hobson; Elizabeth H. Sinclair; Anne E. York; James R. Thomason; Richard E. Merrick (Marine Mammal Science, 2004)
A bstract Stable isotope (δ 15 N and δ 13 C) values of individual tooth annuli of female Steller sea lions ( n = 120) collected from the 1960s through the 1980s were used for retrospective analyses of temporal changes in food webs in the Gulf of Alaska and North Pacific Ocean. We also examined isotopically contour feathers of tufted puffins ( n = 135) and crested auklets ( n = 37) through this period to test for broader isotopic patterns indicative of whole food web changes. Steller sea lions decreased slightly in δ 13 C and increased in δ 15 N values, suggesting an increasing trophic level and change in foraging location or oceanographic isotopic signature. Steller sea lion first and second tooth annuli were enriched in 15 N and depleted in 13 C compared with subsequent annuli, indicating the effects of maternal influence through weaning. The general pattern of increasing δ 15 N values among Steller sea lions supports previous conclusions regarding a reduction or redistribution of forage fishes and an increase of demersal and semi‐demersal species in the North Pacific ecosystem. There were no significant changes in δ 15 N values for either bird species. However, δ 13 C values in both bird species again suggested changes in foraging location or a shift in oceanographic currents.

Sensitivity of Systematic Reserve Selection to Decisions about Scale, Biological Data, and Targets: Case Study from Southern British Columbia - LEANNA D. WARMAN; A. R. E. SINCLAIR; G. G. E. SCUDDER; BRIAN KLINKENBERG; ROBERT L. PRESSEY (Conservation Biology, 2004)
The identification of conservation areas based on systematic reserve‐selection algorithms requires decisions related to both spatial and ecological scale. These decisions may affect the distribution and number of sites considered priorities for conservation within a region. We explored the sensitivity of systematic reserve selection by altering values of three essential variables. We used a 1:20,000–scale terrestrial ecosystem map and habitat suitability data for 29 threatened vertebrate species in the Okanagan region of British Columbia, Canada. To these data we applied a reserve‐selection algorithm to select conservation sites while altering selection unit size and shape, features of biodiversity (i.e., vertebrate species), and area conservation targets for each biodiversity feature. The spatial similarity, or percentage overlap, of selected sets of conservation sites identified (1) with different selection units was ≤40%, (2) with different biodiversity features was 59%, and (3) with different conservation targets was ≥94%. Because any selected set of sites is only one of many possible sets, we also compared the conservation value (irreplaceability) of all sites in the region for each variation of the data. The correlations of irreplaceability were weak for different selection units (0.23 ≤r≤ 0.67), strong for different biodiversity features (r= 0.84), and mixed for different conservation targets (r= 0.16; 0.16; 1.00). Because of the low congruence of selected sites and weak correlations of irreplaceability for different selection units, recommendations from studies that have been applied at only one spatial scale must be considered cautiously.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

Evolutionary relationships of the New Caledonian heterotrophic conifer, Parasitaxus usta (Podocarpaceae), inferred from chloroplast trn L-F intron/spacer and nuclear rDNA ITS2 sequences - W.T. Sinclair; R.R. Mill; M.F. Gardner; P. Woltz; T. Jaffré; J. Preston; M.L. Hollingsworth; A. Ponge; M. Möller (Plant Systematics and Evolution, 2002)

Detecting a genetic bottleneck in Gilbert's Potoroo (Potorous gilbertii) (Marsupialia: Potoroidae), inferred from microsatellite and mitochondrial DNA sequence data - Elizabeth A. Sinclair; Brian Costello; Jacqueline M. Courtenay; Keith A. Crandall (Conservation Genetics, 2002)

Public Involvement in Environmental Assessment: The Case of the Nonparticipant - Alan Diduck; A. John Sinclair (Environmental Management, 2002)

Productivity and profitability of multistrata organic versus conventional coffee farms in Costa Rica - A. E. Lyngbæk; R.G. Muschler; F. L. sinclair (Agroforestry Systems, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Control of Fusarium head blight of wheat with fungicides - M. G. Cromey; D. R. Lauren; R. A. Parkes; K. I. Sinclair; S. C. Shorter; A. R. Wallace (Australasian Plant Pathology, 2001)

Sensitivity of a Standard Host Resistance Assay Using Streptococcus agalactiae for Assessing Exposure to Immunotoxicants in Wild Cotton Rats (Sigmodon hispidus) - L. C. Jones; R. L. Lochmiller; J. A. Sinclair; R. H. Morton (Archives of Environmental Contamination and Toxicology, 2000)

Sensitivity of a Standard Host Resistance Assay Using Streptococcus agalactiae for Assessing Exposure to Immunotoxicants in Wild Cotton Rats ( Sigmodon hispidus ) - L. C. Jones; R. L. Lochmiller; J. A. Sinclair; R. H. Morton (Archives of Environmental Contamination and Toxicology, 2000)

Developmental Plasticity of Postweanling Cotton Rats (Sigmodon hispidus) as an Adaptation to Nutritionally Stochastic Environments - Robert L. Lochmiller; Stephen S. Ditchkoff; John A. Sinclair (Evolutionary Ecology, 2000)

Zonal distribution and seasonal vertical migration of copepod assemblages in the Scotia Sea - A. Atkinson; J. D. Sinclair (Polar Biology, 2000)

The postglacial history of Scots pine ( Pinus sylvestris L.) in western Europe: evidence from mitochondrial DNA variation - W. T. Sinclair; J. D. Morman; R. A. Ennos (Molecular Ecology, 1999)
The geographical structure of mitochondrial (mt)DNA variants (mitotypes) was investigated in 38 western European populations of Scots pine Pinus sylvestris using restriction fragment length polymorphism (RFLP) analysis of total DNA and a homologous cox1 probe. Three major mitotypes (designated a, b and d ) were detected. Within Spain all three major mitotypes were found, gene diversity was high, H T = 0.586, and this diversity was distributed predominantly among rather than within populations ( F ST(M) = 0.813 for the seven Spanish populations). Mitotype d was present only in the most southerly population from the Sierra Nevada . Elsewhere in Europe, populations showed little or no mtDNA diversity within regions, but there were marked differences between regions. Italian populations were fixed for mitotype b ; populations from northern France, Germany, Poland, Russia and southern Sweden were fixed for mitotype a ; while populations in northern Fennoscandia were fixed for mitotype b . The isolated Scottish populations were predominantly of mitotype a , but mitotype b was present in three of the 20 populations scored. In Scotland, UK gene diversity ( H T = 0.120) and genetic differentiation among populations ( F ST(M) = 0.37) was much lower than in Spain. When interpreted in the light of complementary data from pollen analysis and nuclear genetic markers, the results suggest that present‐day populations of P. sylvestris in western Europe have been derived from at least three different sources after glaciation.

Predicting Effects of Predation on Conservation of Endangered Prey - A. R. E. Sinclair; R. P. Pech; C. R. Dickman; D. Hik; P. Mahon; A. E. Newsome (Conservation Biology, 1998)
In parts of the world such as the Pacific Islands, Australia, and New Zealand, introduced vertebrate predators have caused the demise of indigenous mammal and bird species. A number of releases for reestablishment of these mammal species in mainland Australia have failed because predators extirpated the new populations. The nature of the decline of both extant populations and reintroduced colonies provides information on the dynamics of predation. Predator‐prey theory suggests that the effects of predation are usually inversely dependent on density (depensatory) when the prey are not the primary food supply of exotic predators. Thus, such predators can cause extinction of endemic prey species. Three types of evidence can be deduced from the predator‐prey interactions that allow predictions for conservation: (1) whether per capita rates of change for prey increase or decrease with declining prey densities, (2) whether predation is depensatory or density‐dependent, and (3) the overall magnitude of predation. If this magnitude is too high for coexistence, then the degree of predator removal required can be predicted. If the magnitude of predation is sufficiently low, then the threshold density of prey that management must achieve to allow predator and prey to coexist can also be predicted. We analyzed published reports of both declining populations and reintroduced colonies of endangered marsupial populations in Australia. The observed predation curves conformed to the predictions of predator‐prey theory. Some, such as the black‐footed rock‐wallaby ( Petrogale lateralis ), were classic alternate prey and were vulnerable below a threshold population size. Others, such as the brush‐tailed bettong ( Bettongia penicillata ), have a refuge at low numbers and thus offer the best chance for reintroduction. Our predictions suggest a protocol for an experimental management program for the conservation of sensitive prey species: (1) determination of net rates of change of prey with declining population, (2) improvement of survivorship through habitat manipulation, (3) improvement of survivorship through predator removal, (4) determination of the threshold density above which reintroductions can succeed, and (5) manipulations to change interactions from Type II to Type III. The task in the future is to determine how to change the vulnerability of the prey so that they can have a refuge at low numbers. Predicción de los Efectos de la Depredación en la Conservación de una Presa en Peligro de Extinción En algunas partes del mundo como son las Islas del Pacífico, Australia y Nueva Zelandia, los veretebrados depredadores introducidos han ocasionado la desaparición de especies indígenas de mamíferos y aves. Un gran número de liberaciones para el restablecimiento de estas especies de mamíferos en tierras continentales de Australia han fracasado debido a que los depredadores han extirpado las poblaciones nuevas. La naturaleza de la declinación tanto de las poblaciones existentes como de las colonias reintroducidas provee información de las dinámicas de la depredación. La teoría sobre depredador‐presa sugiere que los efectos de la depredación son usualmente inversamente densodependientes (depensatorios) cuando las presas no son el alimento principal de los depredadores exóticos. Por lo tanto, estos depredadores pueden causar la extinción de especies de presas endémicas. Existen tres tipos de evidencia que pueden ser deducidas de las interacciones depredador‐presa y que permiten predicciones para la conservación: 1) que las tasas de cambio per cápita de presas incremente o disminuya con la declinación de las densidades de presas, 2) que la depredación sea depensatoria o densodependiente, y 3) la magnitude total de la depredación. Si la magnitud es muy alta para la coexistencia, entonces el grado de remoción del depredador requerido puede ser predecido. Si la magnitud de la depredación es suficientemente baja, entonces la densidad umbral de la presa que debe ser alcanzado mediante manejo y que permita al depredador y la presa coexistir tambien puede ser predecido. Analizamos reportes publicados tanto de declinaciones de poblaciones como de colonias reintroducidas de poblaciones de marsupiales en peligro de extinción en Australia. Las curvas de depredación observadas se conformaron a la teoría de depredador‐presa. Albunas (i.e. el ualaby, Petrogale lateralis ) fue una clasica presa alternativa y fue vulnerable por debajo del tamaño poblacional umbral. Otras (i.e. Bettongia penicillata ) tiene un refugio de números bajos y ofrece la mejor de las opciones para reintroducciones. Nuestras predicciones sugieren un protocolo para un programa de manejo experimental para la conservación de especies de presas sensitivas: 1) determinación de tasas netas de cambio de presa con población en declive, 2) mejora de la supervivencia mediante la manipualción del hábitat, 3) mejora en la supervivencia mediante remoción de depredadores, 4) determinación de la densidad umbral sobre la cual las reintroducciones podrían ser satisfactorias, y 5) manipulaciones para cambiar interacciones de tipo II y III. La tarea en el futuro será la de identificar el como cambiar la vulnerabilidad de la presa, de tal forma que puedan obtener refugio aún con números bajos.

Predicting Effects of Predation on Conservation of Endangered Prey - A. R. E. Sinclair; R. P. Pech; C. R. Dickman; D. Hik; P. Mahon; A. E. Newsome (Conservation Biology, 1998)

Sensitivity of Wild Cotton Rats ( Sigmodon hispidus ) to the Immunotoxic Effects of Low-Level Arsenic Exposure - M. Savabieasfahani; R. L. Lochmiller; D. P. Rafferty; J. A. Sinclair (Archives of Environmental Contamination and Toxicology, 1998)

Phylogenetic Relationships Within the Genus Potorous (Marsupialia: Potoroidae) Based on Allozyme Electrophoresis and Sequence Analysis of the Cytochrome b Gene - Elizabeth A. Sinclair; Michael Westerman (Journal of Mammalian Evolution, 1997)

Organochlorines and reproductive success of birds in orchard and non-orchard areas of central British Columbia, Canada, 1990?91 - J. E. Elliott; P. A. Martin; T. W. Arnold; P. H. Sinclair (Archives of Environmental Contamination and Toxicology, 1994)

Characterization of an antigenic site on glycoprotein 13 (gC) of equid herpesvirus type-1 - R. Sinclair; B. J. Moult; J. A. Mumford (Archives of Virology, 1993)

New Publications - J. B. Sinclair; Ken Pegg; A. C. Hayward (Australasian Plant Pathology, 1981)

“An annoted bibliography of chickpea diseases 191 5-1 976” - Y. L. Nene; A. Mengitsu; J. B. Sinclair; D. J. Royse (Australasian Plant Pathology, 1978)